The Atlantic outermost regions, the furthest frontiers of Europe? - Valente, Isabel Maria Freitas (Debater a Europa, 2015)
We set out to examine the importance of the Atlantic outermost in the context of the European Union, focusing on the role it plays as an outermost frontier of the European project, and, even more specifically, the Portuguese Autonomous Regions - the Azores and Madeira. http://dx.doi.org/10.14195/1647-6336_12_4